'What do I even call this?' Challenges and possibilities of undertaking a thesis by publication. Issue 9 (20th October 2020) - Merga, Margaret K.; Mason, Shannon; Morris, Julia E.
ABSTRACT: In the current field of doctoral education, there is a range of possible approaches presented to doctoral candidates. The Thesis by Publication (TBP) is an option increasingly offered by universities around the world and adopted by candidates in diverse fields. As the approach gains in popularity in response to the demands of modern academia, there is a need to better understand the limitations and possibilities associated with completing a TBP. This paper reports on a survey of 246 recently conferred doctoral candidates from Australian universities, who shared their personal experiences of successfully completing a TBP, with particular focus on the challenges and benefits. The challenges of ensuring thesis cohesion, time pressures, managing the publishing journey, and issues with supervisory and/or university support emerged as notable recurring themes. Positives included efficiency, accessibility and dissemination of findings, feedback, skills for research, career and reputation, emotion and motivation, and ease of examination. These findings have associated implications for candidates seeking to make informed choices about the approach that best suits their needs. They can also inform supervisors desirous of supporting students to harness the benefits and overcome the challenges of the TBP, and support institutions in the provision of informed and responsive guidelines and training opportunities for TBP.